Menilik Potret Tantangan Dalam Menyongsong Pemilu Serentak 2024 - Nimah, Rodhotun (Muhammadiyah Law Review Journal, 2024)
The simultaneous holding of the general election on April 17, 2019, marks a new chapter in the electoral process in Indonesia. This development is the result of the Constitutional Court Decision Number 14/PUU/2013, which reviewed Law Number 42 of 2008 concerning the Election of the President and Vice President. Despite the acknowledgment that simultaneous elections are considered an improvement compared to previous ones, it doesn't mean that the implementation is flawless. The most alarming issue is the significant loss of lives among election organizers, seen as a consequence of the 2019 simultaneous elections, along with other technical problems. Considering the various aspects arising from the 2019 elections, it is essential to reevaluate whether simultaneous elections are ideal for Indonesia's governance. This research is of a juridical-normative nature, utilizing a legal approach and case analysis. The data collection technique and arguments presented in this paper rely on qualitative studies. The findings of this research state that simultaneous elections represent a new breakthrough for Indonesian democracy, but there are still specific areas that require special attention. In this regard, the Constitutional Court proposes alternative models for simultaneous elections that can be chosen and deemed constitutional based on the 1945 Constitution.